Consumer Motivation and Online Information Credibility - Asih, Rayi Retno Dwi; Magetsari, Ovy Noviati Nuraini; Sumardi, Arwini (Indonesian Management and Accounting Research, 2022)
The government continues to strive to make Indonesia a mecca for world Muslim fashion, stated the Director of Chemical, Clothing, Handicraft and Miscellaneous IKM, Ministry of Industry Ratna Utarianingrum . The axis of the emergence of fashion is the city of Bandung, Tasikmalaya , and Kudus. Increasing the presence of the textile manufacturing industry to textile products (TPT) from downstream to upstream continues to be pursued. This can be achieved by the existence of supporting factors, including the number of designers, business and fashion universities which will produce many young creative designers. This research was conducted over a period of 10 (ten) months, starting in October 2021 and finished in July 2022. The research location is in Jakarta, Indonesia. This study refers to previous research and the research design is a hypothesis testing that aims to test existing hypotheses by explaining the characteristics of certain relationships or influences, by looking at differences between groups or interpretations of two or more factors in a situation.